Knowledge and Practice of Vitamin D Deficiency and Risk of Depression Among Population in Makkah City, Saudi Arabia - Rimah Dagnah, Ozuf Alotaibi, Nada Ali Alasmari, Bayan Alsulami, Bashaer Alzamzami, Yosra Alhindi (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Depression can be correlated with severe disability, mortality, and significant healthcare costs. It is the third leading cause of disability in worldwide affecting around 840 million people1. Vitamin D, which is a distinctive hormone with target receptors found in many areas in the body and in human brain, plays an important role in the development of depression through many physiological processes. In Saudi Arabia we found that the prevalence of depression is high, however, the exact cause is unknown. Moreover, there are many risk factors that can trigger the onset of depression such as chronic infection diseases, low socio-economic statue, stressful life events, family history, traumatic experience, all these associated with risk of depression. Objective: The aim of the study was to identify and to assess the knowledge and practice of vitamin D deficiency and risk of depression among the adult population in Makkah city. Methods: This is a cross-sectional descriptive study that was done in Makkah holey city, in the western region of Saudi Arabia. Results and conclusions: The majority of this study’s participants were familiar with vitamin D, with the media serving as the most prevalent source of this information. Our participants also had substantial experience with vitamin deficiency. Similarly to a study conducted in Riyadh, our findings showed that medical experts were the most often cited information source. Overall, we found that the group we examined had a strong grasp of the relationship between vitamin D insufficiency and the recognition of depressive symptoms and put that understanding into practise. Additional research into the correlation between vitamin D and depression is warranted. Keywords: Vitamin D, Depression, Knowledge, Practice, Makkah.